Associations of Depressive Symptoms, COVID-19-Related Stressors, and Coping Strategies. A Comparison Between Cities and Towns in Germany - Meyer, Caroline; El-Haj-Mohamad, Rayan; Stammel, Nadine; Lotzin, Annett; Schäfer, Ingo; Knaevelsrud, Christine; Böttche, Maria (Frontiers in Psychiatry, 2022)
Background. The COVID-19 pandemic has led to a wide range of stressors related to depressive symptoms. Prevention measures like physical distancing have burdened the general population, especially in highly urbanized areas. However, little is known about the associations between pandemic-related stressors, coping strategies, and depressive symptoms in highly urbanized vs. less urbanized environments. Methods. Participants were recruited in a cross-sectional online survey in Germany. Propensity score matching yielded a matched sample of city (n = 453) and town (n = 453) inhabitants. Depressive symptoms, COVID-19-related stressors, and coping strategies were compared between cities and towns. Multiple regression analysis was performed to determine associations between pandemic-related stressors and depressive symptoms for the two groups separately. Results. City inhabitants showed significantly higher depression scores than town inhabitants (t = 2.11, df = 897.95, p = .035). Seven coping strategies were more often used by the city sample. Depressive symptoms were associated with ‘restricted physical social contact’ and ‘difficult housing conditions’ (adjusted R² = .19, F[9, 443] = 12.52, p < .001) in city inhabitants, and with ‘fear of infection’ and ‘difficult housing conditions’ (adjusted R² = .20, F[9, 443] = 13.50, p < .001) in town inhabitants. Limitations. The data were collected at the end of the first wave and represent a snapshot without causal inferences. Pandemic-related stressors were measured with a newly developed scale. Conclusion. Depressive symptoms, perceived stressors, and approach/avoidance coping strategies differed between city vs. town inhabitants. These differences should be considered in policy-making and mental health care.